The story of Queen Tribhuwana Wijayatunggadewi As Source of Ideas for Designing Majapahit Batik Motifs - Rismawati, Aristya Rizky Rismawati; Indarti, Indarti (Practice of Fashion and Textile Education Journal, 2024)
Queen Tribhuwana Wijayatunggadewi was one of the leading female rulers and played a significant role in organizing and expanding Majapahit’s territory. This research aims to find out 1) the process of designing Majapahit batik motifs with the source of ideas from the story of Ratu Tribhuwana Wijayatunggadewi, 2) the resulting Majapahit batik motifs with the source of ideas from Queen Tribhuwana Wijayatunggadewi. The method used is the Double Diamond Model which consists of 4 stages, namely discover, define, develop and deliver. In the initial stage, summarize the sources of ideas to create a moodboard with a predetermined theme which leads to batik motif designs. The second stage is developing a moodboard that has been made into several stylizations. The third stage is arranging the stylization into 6 batik motif developments. The fourth stage is the process of producing a prototype of one of the Majapahit batik designs with the source of the idea being Queen Tribhuwana Wijayatunggadewi. This research produced 6 batik motif designs for the story of Queen Tribhuwana Wijayatunggadewi, and of these 6 designs, 1 design was selected which was realized in the form of batik cloth with the story motif of Queen Tribhuwana Wijayatunggadewi with a cloth size of 200 x 115 cm.